MODERNIST CURRENTS IN THE LITERATURE OF THE XX CENTURY FEATURES OF FUTURISM AND ITS VARIETIES (Scientific journal of the Fergana State University, 2023)
In the article, the author reveals futurism as one of the contradictory avant-garde treads in literature, new phenomena in language and literature, connected by the poetic views of the futurists, their theoretical platform.